If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1q + -13 = 2q + 5 Reorder the terms: -13 + -1q = 2q + 5 Reorder the terms: -13 + -1q = 5 + 2q Solving -13 + -1q = 5 + 2q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-2q' to each side of the equation. -13 + -1q + -2q = 5 + 2q + -2q Combine like terms: -1q + -2q = -3q -13 + -3q = 5 + 2q + -2q Combine like terms: 2q + -2q = 0 -13 + -3q = 5 + 0 -13 + -3q = 5 Add '13' to each side of the equation. -13 + 13 + -3q = 5 + 13 Combine like terms: -13 + 13 = 0 0 + -3q = 5 + 13 -3q = 5 + 13 Combine like terms: 5 + 13 = 18 -3q = 18 Divide each side by '-3'. q = -6 Simplifying q = -6
| -1+3p=-1p-5p | | 8=4z-3z^2+15 | | x-12=48 | | -5x-2=4-4x | | 5p+6p-y-2p+4y= | | 5*n-7=38 | | 6m-3=-10-6(2-m) | | t+5t+4t-7=17 | | 4-3a=8-4a | | 1x+2=32x-160+80x-70 | | 4x+5/2x+3 | | 5x^2+15x+90=0 | | 7*y-3*y-14=14 | | -x-3x+5=4x+5 | | 2x+4/2x+3 | | 18x^2-48x-50=0 | | 10+-1=25 | | 8+3n=4n+2 | | X^3-18=9x-2x^2 | | -5=-14+7 | | a/4-7=10 | | 3x-3(-4x+12)=9 | | -9a^9+(-7a^9-5)= | | x^2+71=-18x-9 | | 2/2-x=x+1/1-x | | 13(-2)-4y=-66 | | 3x+2.1=0 | | 8x+4-7x=8-22 | | 4x^2-64x=192 | | 2*3(9y+3)=4y+7 | | 3k-9=6-2k | | x^2+9x+18=x+3 |